2009
DOI: 10.1001/jama.2009.1855
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Oxygen for Treatment of Cluster Headache

Abstract: LUSTER HEADACHE IS A STEREOtypical primary headache syndrome characterized by attacks of unilateral excruciating pain usually in the eye, periorbital region, and temple with associated cranial autonomic symptoms such as conjunctival injection, lacrimation, nasal blockage, rhinorrhea, ptosis, and eyelid edema. During attacks patients are often restless, agitated, or both. Attacks typically last for 15 to 180 minutes untreated and have a frequency of 1 every other day for up to 8 attacks a day. 1 Attacks usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(194 citation statements)
references
References 23 publications
(28 reference statements)
2
180
1
4
Order By: Relevance
“…Cohen et al evaluated the effectiveness of using 12-15 L/min oxygen for treatment of CH. 115 While headache relief was comparable to studies using lower flows, no rebound CH were reported.…”
Section: Cluster Headachementioning
confidence: 65%
“…Cohen et al evaluated the effectiveness of using 12-15 L/min oxygen for treatment of CH. 115 While headache relief was comparable to studies using lower flows, no rebound CH were reported.…”
Section: Cluster Headachementioning
confidence: 65%
“…The most important one is low participant number and inability. Most studies on oxygen therapy in treatment with pain ranged from 15 to 70 min, [14][15][16] and most studies of InHO in neuroscience designated 4 h per day for six consecutive days (almost a week) as their treatment. 21,22,34 We regarded daily term (1 h per day, 2 h per day and 4 h per day) and weeks (1 week, 2 weeks and 4 weeks) of InHO therapy as factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have reported that oxygen therapy appears to be effective in the pain management and show same effectiveness as hyperbaric oxygen. [14][15][16] Though studies have revealed the analgesic effect of hyperbaric oxygen in both rats and human with neuropathic pain, 13,[17][18][19] costs and poor availability limit the use of hyperbaric oxygen. These prompt us to investigate the effect of intermittent normobaric hyperoxia (InHO) in the treatment of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…For acute attack, High-flow oxygen (10-12 L/ min for 15-20 min) or sumatriptan (6 mg SC or 20 mg nasal spray) is effective. 30 Deep-brain stimulation of the posterior hypothalamic gray matter is successful for refractory cases as is the less-invasive approach of occipital nerve stimulation. Hemicrania continua is a continuous, strictly unilateral headache that waxes and wanes .…”
Section: Cluster Headache Treatmentmentioning
confidence: 99%